The lived experience of women with a bleeding disorder: A systematic review. Issue 1 (3rd February 2022) - Sanigorska, Anna; Chaplin, Steve; Holland, Mike; Khair, Kate; Pollard, Debra
Abstract: Background: Research studies have described the morbidity associated with inherited bleeding disorders such as hemophilia and von Willebrand disease in women, but their effect on daily living has long been underrecognized. This systematic review sought to document the lived experience of women with a bleeding disorder by assessing research findings on quality of health care, socioeconomic factors, and mental health. Methods: A systematic search was carried out in Web of Science, the Cumulative Index to Nursing and Allied Health Literature, and PubMed on July 31, 2020. References were hand searched. Abstracts of the 2019 and 2020 congresses on bleeding disorders were hand searched. Key journals were screened for relevant studies published after the search date until the analysis was completed on December 7, 2020. Results: Of 635 potentially eligible publications, 27 published since 1998 were selected for review. Most studies were of moderate to high quality but meta‐analysis of quantitative studies was not possible due to difference in outcomes and assessment. Women with a bleeding disorder experience obstacles to accessing care, difficulties living with their disorder, interference with schooling and work, and poor mental health. Diagnostic delay and lack of recognition of symptoms mean treatment and support may not be available. Where comparisons with controls were made, women's negative experiences were greater than those of men. Conclusions: Women with bleeding disorders experience major negative impacts of their disorders on daily life and mental well‐being. Many of the challenges identified in earlier research are evident in more recent studies.